PWE-182 Mortality After Peg: Review of 259 Peg Procedures at a District General Hospital over A 7 Year Period. (4th June 2013) - Thavanesan, K; Barnett, K; Harding, S; Hartley, D; Al-Shamma, S; Weaver, S A; McLaughlin, S D
Abstract : Introduction: Percutaneous Endoscopic Gastrostomy (PEG) is commonly performed in patients that require medium to long-term enteral feeding. In 2004 NCEPOD reviewed the 30day mortality and rate of complications following therapeutic endoscopy. They reported a 6% 30 day mortality and made recommendations regarding changes in practise. Nationally there is little published data on the 1 year mortality following this procedure. In 2010 we introduced changes to our practise including: 1. The review of all PEG referrals by a nutrition team, 2. Stringently avoiding PEG for 2 weeks following stroke, 3. Avoiding PEG in patients with pneumonia or other inter-current illness. Aim: to review the 30day and 1 year mortality following PEG at our institution since the NCEPOD publication. Methods: A prospective endoscopy database is maintained at our institution (HICCS). We searched the database for primary PEG procedures during the period of Jan 2005 to September 2012 and reviewed electronic medical records to establish the overall 30 day and 1 year mortality, and also mortality by indication. Results: A total of 259 procedures were performed. Indications were: Stroke n = 130 (50%), Multiple sclerosis (MS) n = 28 (10.85%), Motor neurone disease (MND) n = 19 (7.36%). Mortality data is given in table 1 . Overall 30 day mortality by indication was: Stroke 10.8%, MND, 6.3%, MS 12.5% 1 year mortality: Stroke 31.27%, MND 50.0%, MS 30.7%. Conclusion: Stroke is the commonest indication for PEG at our hospital. The mean annual 30day mortality following PEG at our hospital is above that reported by NCEPOD but has fallen considerably since 2010 suggesting that changes in our practise have been effective. 1 year mortality in MND patients is high and emphasises the importance of careful patient selection. We recommend that other institutions with a high 30 day mortality following PEG adopt the changes in practise outlined above. Ongoing audit of our practise is required. Disclosure of Interest: None Declared.